Pengaruh Project Based Learning Materi Kepemimpinan Sultan Trenggono terhadap Kognitif Siswa Kelas X - Viqy Awlia El Haqque; Atno (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The objective of this study is to analyze the effect of implementing the Project Based Learning (PjBL) model on the cognitive learning outcomes of Grade X students at MA Asy-Syarifah on the topic of the Leadership of Sultan Trenggono in the Demak Sultanate. This research employed a quasi-experimental method with a pretest-posttest control group design. The sample consisted of two classes, namely an experimental class that implemented the Project Based Learning (PjBL) model and a control class that used conventional teaching methods. The instrument used for data collection was a learning achievement test. The results of this study indicate a significant increase in students’ learning outcomes in the experimental class compared to the control class. The paired t-test showed that both classes experienced a significant increase in scores (p < 0.001), but the experimental class achieved a higher gain. In addition, the independent t-test revealed a significant difference between the posttest scores of the two classes (p < 0.001). Based on these findings, it can be concluded that the implementation of the Project Based Learning (PjBL) model is effective in improving students’ cognitive learning outcomes in history lessons. Keyword: Project-Based Learning, Student Cognitive Ability, Sultan Trenggono's Leadership.